2019
DOI: 10.1002/humu.23779
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in TIMM50 cause severe mitochondrial dysfunction by targeting key aspects of mitochondrial physiology

Abstract: 3‐Methylglutaconic aciduria (3‐MGA‐uria) syndromes comprise a heterogeneous group of diseases associated with mitochondrial membrane defects. Whole‐exome sequencing identified compound heterozygous mutations in TIMM50 (c.[341 G>A];[805 G>A]) in a boy with West syndrome, optic atrophy, neutropenia, cardiomyopathy, Leigh syndrome, and persistent 3‐MGA‐uria. A comprehensive analysis of the mitochondrial function was performed in fibroblasts of the patient to elucidate the molecular basis of the disease. TIMM50 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 57 publications
8
19
0
1
Order By: Relevance
“…Similar results were found in patients with heterozygous mutations in Tim50 R114Q and G269S who present with 3-MGA-uria, a generalised reduction in the activity and assembly of the Accepted Article respiratory chain complexes, reduced respiration and aberrant cristae [99]. Patients with heterozygous Tim50 mutations (S112* and G190A; R114Q and G269S) also had reduced Tim50 protein levels, potentially contributing to the observed heterozygous patient phenotypes [97,99]. The variable effects on protein import, respiration and severity of disease progression may be a consequence of the specific mutation and how that mutation affects protein structure and function.…”
Section: Tim50 and 3-methylglutaconic Aciduria Type IXsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results were found in patients with heterozygous mutations in Tim50 R114Q and G269S who present with 3-MGA-uria, a generalised reduction in the activity and assembly of the Accepted Article respiratory chain complexes, reduced respiration and aberrant cristae [99]. Patients with heterozygous Tim50 mutations (S112* and G190A; R114Q and G269S) also had reduced Tim50 protein levels, potentially contributing to the observed heterozygous patient phenotypes [97,99]. The variable effects on protein import, respiration and severity of disease progression may be a consequence of the specific mutation and how that mutation affects protein structure and function.…”
Section: Tim50 and 3-methylglutaconic Aciduria Type IXsupporting
confidence: 76%
“…3-Methylglutaconic aciduria (3-MGA-uria) syndromes comprise a group of diseases with elevated 3-MGA-uria in urinary secretions and mitochondrial membrane defects ( Table 1). A variety of mutations (missense and nonsense) in Tim50 result in the autosomal recessive disorder 3-MGA-uria type IX (MGCA9), which is characterised by early onset seizures, 3-MGA-uria, intellectual disability and delayed development, and hypotonia or spasticity [97][98][99]. Reyes et al, (2018) identified a patient with heterozygous mutations in Tim50 (S112* and G190A), levels of Complex I, II and IV respiratory components were reduced, decreased respiration and increased reactive oxygen species (ROS) [97].…”
Section: Tim50 and 3-methylglutaconic Aciduria Type IXmentioning
confidence: 99%
“…7a). We found that the ability of PPARα signaling to shorten CTD is significantly impaired when targeting genes encoding SF3B2/SAP18 (RNA splicing factors) 39,40 , and TIMM50 (a mitochondrial translocase) 41 (Fig. 7b-c, Fig.…”
Section: Resultsmentioning
confidence: 91%
“…This analysis identified 148 genes directly regulated by PGC1/PPARα ( Figure 4G and Table S1). They included several novel targets of PGC1/PPARα with unknown roles in CM maturation, including genes encoding Yap1, a transcriptional effector of Hippo signaling with crucial roles in cardiac regeneration (Xin et al, 2013), SF3B2/SAP18, RNA splicing factors (Golas et al, 2003;Singh et al, 2010), TIMM50, a mitochondrial translocase regulating mitochondrial function (Tort et al, 2019), and STRIP1, a core component of the striatin-interacting phosphatases and kinase complex regulating cell contractility (Suryavanshi et al, 2018).…”
Section: Pgc1/pparα Regulates Genes Affecting Cell Size Calciummentioning
confidence: 99%